Blueprint for harmonising unstandardised disease registries to allow federated data analysis: prepare for the future. Issue 4 (4th October 2022) - Kroes, Johannes A.; Bansal, Aruna T.; Berret, Emmanuelle; Christian, Nils; Kremer, Andreas; Alloni, Anna; Gabetta, Matteo; Marshall, Chris; Wagers, Scott; Djukanovic, Ratko; Porsbjerg, Celeste; Hamerlijnck, Dominique; et al.
Real-world evidence from multinational disease registries is becoming increasingly important not only for confirming the results of randomised controlled trials, but also for identifying phenotypes, monitoring disease progression, predicting response to new drugs and early detection of rare side-effects. With new open-access technologies, it has become feasible to harmonise patient data from different disease registries and use it for data analysis without compromising privacy rules. Here, we provide a blueprint for how a clinical research collaboration can successfully use real-world data from existing disease registries to perform federated analyses. We describe how the European severe asthma clinical research collaboration SHARP (Severe Heterogeneous Asthma Research collaboration, Patient-centred) fulfilled the harmonisation process from nonstandardised clinical registry data to the Observational Medical Outcomes Partnership Common Data Model and built a strong network of collaborators from multiple disciplines and countries. The blueprint covers organisational, financial, conceptual, technical, analytical and research aspects, and discusses both the challenges and the lessons learned. All in all, setting up a federated data network is a complex process that requires thorough preparation, but above all, it is a worthwhile investment for all clinical research collaborations, especially in view of the emerging applications of artificial intelligence and federated learning. Harmonising real-world patient data from diverse registries to allow federated analyses is a complex process that requires thorough preparation but is above all a valuable investment, especially in view of emerging applications of artificial intelligence https://bit.ly/3NEKKnV